English language teaching for Autism Spectrum Disorders (ASD) learners during pandemic era - Sophya, Ida Vera (ELT Forum: Journal of English Language Teaching, 2021)
An Autistic child is a child who has special needs and developmental disorders. Therefore, in the teaching learning process, teachers who teach ASD learners need to have some knowledge of students’ needs. The objections of this study are to explain the implementation of English language teaching for ASD learners during the pandemic era and parents’ role in helping ASD learners understand English. This research employed qualitative research. The researchers applied observation, depth interview and documentation in data collection. The results showed that 1) the English language teaching process for ASD at RBA during the pandemic era applied offline and online learning mode. The material of English language teaching for ASD learners was based on the level of ASD diagnosis. The teachers used direct method, TPR, and Lexical method in offline learning, but for online learning, they used Direct and lexical methods. The teachers also utilised pictures or flashcards in offline learning whereas for online learning they gave the students worksheets and did a video call. In giving assessment, the teachers carried out anecdotal notes, checklists, interviews, and retelling stories 2) During the pandemic era, the role of ASD parents was to accompany their child at home pronouncing English vocabularies that had been given by the therapist at RBA. On the other hand, in on-line learning, the role of parents was as a teacher/therapist who gave treatment to their children at home based on therapists’ instructions.